Distribution of Eimeria uekii and Eimeria raichoi in cage protection environments for the conservation of Japanese rock ptarmigans (Lagopus muta japonica) in the Japanese Alps. - 芝原, 友幸; シバハラ, トモユキ; SHIBAHARA, Tomoyuki (International Journal for Parasitology: Parasites and Wildlife, 2021)
journal article